Child Development - Santrock, John W. (Boston : McGraw-Hill, 2007)
"Thorough. Accurate. Reliable. Engaging. These are just a few of the words used by adopters and reviewers of John Santrock's Child Development. A new Connections theme shows how it all fits together in the the most accurate and up-to-date topically-organized text in the field. Used by hundreds of thousands of students over twelve editions, Santrock's proven learning system provides a clear roadmap to content mastery. The fully revised thirteenth edition continues with Santrock's highly contemporary tone and focus, featuring over 1,000 new citations"--
Includes bibliographical references and index (p. NI.1-SI.9).
Keywords: Child development; Child psychology